(untitled) (Perner’s Contacts, 2023)
Although the economic development of the Czech Republic in the past decade can be assessed as entirely positive, the development of the performance of domestic road freight carriers showed a sharp decline during the same period. However, European road truck transport was forced to solve an extensive range of problems, which had a noticeable impact on domestic carriers. The presented paper aims to find and indicate the causes of this development and point out some factors that helped to reverse the unfavorable development.